Digital Readiness, Agility, and Creativity as Drivers of Competitive Advantage in the Creative Industry - Asti Nur Aryanti; Christianingrum Christianingrum (International Journal of Applied Business and International Management, 2026)
This study examines the role of digital readiness in enhancing the competitiveness of creative industry MSMEs by analyzing its relationship with digital agility and digital creativity. It specifically investigates how digital readiness directly and indirectly influences digital competitiveness through the mediating roles of digital agility and digital creativity. Using a quantitative approach with Structural Equation Modeling (SEM), this study analyzes data from micro, small, and medium enterprises (MSMEs) operating in the creative industry sector, particularly the fashion, culinary, and craft subsectors, in West Java, Indonesia. The findings reveal that digital readiness significantly influences digital agility, digital creativity, and digital competitiveness. Digital agility positively affects both digital creativity and digital competitiveness, while digital creativity significantly contributes to strengthening digital competitiveness. The results also indicate that digital agility and digital creativity jointly mediate the relationship between digital readiness and digital competitiveness. These findings suggest that digital readiness serves as a fundamental capability that enables MSMEs to adapt quickly to digital transformation, stimulate creativity, and improve their competitiveness in digital markets. The integration of readiness, agility, and creativity forms a strategic synergy that supports the sustainability and competitive advantage of creative industry businesses. This study contributes to the literature by developing an integrated framework linking digital readiness, digital agility, and digital creativity to digital competitiveness within the MSME creative industry context. Practically, the findings offer insights for MSME managers and policymakers to strengthen digital infrastructure, develop digital competencies, and encourage innovative practices to improve competitiveness in the digital economy. Its novelty lies in proposing a comprehensive digital competitiveness model that positions digital agility and digital creativity as key mediating mechanisms linking digital readiness to competitive advantage in the creative industry.